Subgroups of Adolescent Girls with Borderline Personality Disorder Symptoms - Slavin-Stewart, Claire (My University, 2015)
This thesis examined the borderline personality disorder symptom profiles of teenage girls who were referred to a tertiary child and youth psychiatry clinic. Self-injury and unstable mood are key features of Borderline Personality Disorder (BPD) but are also associated with other disorders such as depression and anxiety disorders. The aim of the larger study was to determine whether BPD can be differentiated from other disorders in a highly comorbid adolescent sample who self-injure. To answer this question, individuals in our sample were grouped based on the pattern of BPD symptom endorsement using a latent class analysis. The subgroups that emerged from our sample were then compared to each other across other clinical measures. Four latent classes were identified. The most impaired class had a high prevalence of BPD (70%). An intermediate class had a significantly higher prevalence of PTSD (41.7%). Another intermediate group had a higher prevalence of anxiety disorders (62%) (Social Phobia and Generalized Anxiety Disorder). The largest class had a low prevalence of all psychiatric disorders. The results indicated that only a small subset of teenage girls who presented with self-injury and unstable mood met criteria for BPD. These girls represented a distinct and severely impaired group with high comorbidity. The subgroups that emerged from our sample provide guidance to clinicians regarding the likelihood of a personality disorder diagnosis in this population and the pattern of emotional difficulties of youth who self-injure.
Keywords: Borderline Personality Disorder; Depression; Self-injury; Unstable mood